Pengembangan Bahan Ajar Multimedia Interaktif Berbasis Canva pada Materi Fiqih Ibadah Haji dan Umrah - Ismail, Rizal Nurdin; Astutik, Anita Puji (LITERATUS, 2024)
Learning innovation has become a serious problem after the arrival of the Covid 19 pandemic. This happened because of the restrictions on social activities as a whole, including in the education sector. Education during the Covid 19 pandemic forced teachers to make various innovations in the design of learning materials so that students could receive learning well. Including the subject of Islamic Religious Education, it also requires innovative teaching materials so that it can be more interesting in learning to students. As is the case with fiqh material, the chapter on Hajj and Umrah will be more attractive to students if collaborated with innovative teaching material designs. In this case the author tries to collaborate the fiqh material on the chapter of Hajj and Umrah with the Canva editing application. So that the delivery of fiqh material on the chapter of Hajj and Umrah will be in the form of a semi-application. So that the delivery of teacher material will not only be verbal but also by utilizing multimedia-based teaching material design. This research is a development research (Research and Development (R&D)) with the aim to explore information about the development of the object of research and improve its development. The research procedure uses the ADDIE model which includes four stages; Analysis, Design, Development, Implementation, and Evaluation. A canva application can increase the effectiveness of religious learning, ensuring that students not only understand important material in Islam, but also feel engaged and motivated.